Multiple cutaneous reticulohistiocytoma in middle aged female - Manish Bansal; Kajal Manchanda; Shyam S Pandey (Wolters Kluwer Medknow Publications, 2014)
Multiple cutaneous reticulohistiocytoma (MCR) and multicentric reticulohistiocytosis (MR) are rare, idiopathic histiocytic granulomatous disorders presenting in a spectrum. A 35-year-old female presented with multiple, firm, discrete, asymptomatic nodules, 1-2 cm in size over face, back, abdomen, thighs, and legs. There were no systemic symptoms. Histopathology of a nodule over trunk showed diffuse, dense infiltrate of large histiocytes, and histiocytic giant cells. The histiocytes had rounded vesicular nuclei and abundant pink homogenously stained ground glass cytoplasm. The diagnosis of MCR was made. Systemic evaluation did not reveal any abnormality. Considering the cosmetic appearance of facial lesions, patient was referred to the plastic surgeon. No treatment was advised for rest of lesions and patient was asked to review every 6 months or if any new complaints develop.